Nirergative Verbs in Novels "Laskar Pelangi" by Andrea Hirata and "Perempuan Berkalung Sorban" by Asma Nadia - Mega Williandani; Mulyadi Mulyadi (Randwick International of Education and Linguistics Science Journal, 2024)
This study aims to compare the use of niergative verbs in two famous novels in Indonesian literature, namely "Laskar Pelangi" by Andrea Hirata and "Perempuan Berkalung Sorban" by Asma Nadia. Nirergative verbs, which do not require an object in the sentence, play an important role in stretching the story and characters in a narrative. This study analyzes the context of the use of nirergative verbs in the two novels, focusing on their influence on plot development, characterization, and theme. The results of the analysis show differences in the use of nirergative verbs in the two novels. "Laskar Pelangi" tends to use nirergative verbs to describe the character daily lives in the context of their school and neighborhood. On the other hand, "Perempuan Berkalung Sorban" emphasizes the use of nirergative verbs to explore the spiritual aspects and internality of its main characters, creating a more introspective feel. This study also discusses the implications of the use of nirergative verbs on the reader's understanding of the narrative and the message the author wants to convey. This comparison reveals that although both novels use nirergative verbs to achieve different literary effects, they both succeed in creating immersive stories and make significant contributions to Indonesian literature. This comparison provides a deeper insight into the use of non-nergative verbs in Indonesian literature and how their use can affect the narrative and the reader's understanding.